2021
DOI: 10.1002/aenm.202102148
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Defects to the Formation and Growth of Li Dendrite in All‐Solid‐State Batteries

Abstract: The nucleation and growth of Li metal during deposition and the associated dendrite penetration are the critical and fundamental issues influencing the safety and power density of solid‐state lithium metal batteries (SSLBs). However, investigations on Li metal deposition/dissolution especially the formation and growth of Li dendrites and their determining factors in the all‐solid‐state electrochemical systems are still lacking. In this work, in situ observations of the Li metal growth process, and defects indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 65 publications
1
64
1
Order By: Relevance
“…[116] Furthermore, interface defects can act as penetration sites for dendrite nucleation and growth. [117,118] So, engineering a passage layer to render tight contact between electrode and SSE is needed. Several methods have been investigated to address interfacial resistance: space charge layer (SCL) formation, which includes direct co-sintering of cathode and solid electrolyte, or in-situ synthesis of solid electrolyte and cathode.…”
Section: Interfacial Modificationmentioning
confidence: 99%
“…[116] Furthermore, interface defects can act as penetration sites for dendrite nucleation and growth. [117,118] So, engineering a passage layer to render tight contact between electrode and SSE is needed. Several methods have been investigated to address interfacial resistance: space charge layer (SCL) formation, which includes direct co-sintering of cathode and solid electrolyte, or in-situ synthesis of solid electrolyte and cathode.…”
Section: Interfacial Modificationmentioning
confidence: 99%
“…[39] A recent study from Yang's group clearly demonstrates that these SE defects exhibit faster Li deposition kinetics and high nucleation tendency. [40] Nevertheless, given the scale and extent of the currently discovered reaction hot-spots (Figure 4h) it is suggested that further dedicated studies on ionic conduction path, [41] electron conduction, [14] and/ or electric field distribution [38] in ASSBs are desirable. [42]…”
Section: Mechanical Deformation Of the Se After Extended Cyclesmentioning
confidence: 99%
“…The results showed that the Li deposition sites and growth pattern depend strongly on the quality of the electrolyte substrate and are closely related to the defects (pores, grain boundaries, impurity phases) within the electrolyte. 43 Moreover, Sun et al directly observed lithium dendrite formation within the Li 3 PS 4 electrolyte. They attributed the formation of lithium dendrite to P- and S-based crystalline defects in the solid-state-electrolyte, which was verified by the use of cryo-transmission electron microscopy morphologies and theoretical calculations.…”
Section: Dendrite Growth Mechanism Of Lithium Metal Anodesmentioning
confidence: 99%